An Unusual Case of Perforated Appendicitis in Situs Inversus Totalis in Indonesia (The New Ropanasuri Journal of Surgery, 2022)
Situs inversus is a rare congenital anomaly where the internal organs are transposed in a mirror image. It is commonly unrecognized until a patient comes with a complaint, especially in developing countries where people do not have a routine medical checkup. We report a case of a young female with unusual left lower quadrant pain abdominal pain. Perforated appendicitis leading to peritonitis was confirmed using ultrasonography and successfully treated with laparotomy. Appendicitis should be considered a working diagnosis in lower left quadrant abdominal pain